1996
DOI: 10.1177/112067219600600316
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Pars Plana Vitrectomy and Silicone Oil for Giant Tears

Abstract: PPV with SOI proved highly effective in GT. Proliferative vitreoretinopathy was the main cause of surgical failure and a frequent obstacle to silicone oil removal. The risks of redetachment have to be evaluated especially carefully when dealing with the only eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…In this study, 43% of the eyes had a postoperative VA of Յ0.1, while Karel et al, 24 who also studied patients after a longer follow-up period, found that 70% had a VA Յ0.1 (Table 4). In our study 57% of the patients had a postoperative VA better than 0.1, and 60% had an equal or better postoperative VA than preoperative, which is comparable to results reported earlier by others.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In this study, 43% of the eyes had a postoperative VA of Յ0.1, while Karel et al, 24 who also studied patients after a longer follow-up period, found that 70% had a VA Յ0.1 (Table 4). In our study 57% of the patients had a postoperative VA better than 0.1, and 60% had an equal or better postoperative VA than preoperative, which is comparable to results reported earlier by others.…”
Section: Discussionmentioning
confidence: 76%
“…In other studies, the percentage of eyes from which the silicone oil was not removed at the end of the follow-up period was much higher 5,24,32 (Table 4). For instance, Scott et al 32 reported that in their series 41% still had silicone oil tamponade at the end of the follow-up period (Table 4).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Due to their high surface tension, retinal breaks can be closed internally, without the heavy liquid flowing into the subretinal space. Glaser et al 16 showed that, in GRTs complicated by severe PVR, the use of heavy liquids to flatten the retina followed by longacting gas tamponade yielded a significantly better outcome compared to fluid air exchange and silicone oil tamponade. Similarly, they also demonstrated the efficacy of heavy liquid flattening of GRTs with inverted flaps in the absence of PVR.…”
Section: Resultsmentioning
confidence: 99%
“…14 The use of perfluorocarbons (heavy liquids) as an adjunctive tool has made unfolding and stabilisation of the retina easier. 15,16 The use of silicone oil has also been proven to be more effective in early visual rehabilitation, 17 and is also safer to exchange with perfluorocarbons.…”
mentioning
confidence: 99%